On the energies of a bounded Coulomb potential - Fernández, Francisco Marcelo (2010)
We discuss recent results for a confined Coulomb model obtained by means of the asymptotic iteration method. Here, we apply the Riccati?Padé method that is based on a rational approximation to a modified logarithmic derivative of the wavefunction. We improve those earlier results and argue that the model may not be useful for actual physical applications.